Crossing Frontiers : Bold, Brave & Beyond - Azwan, Abidin; Noorhaslina, Senin (UNIMAS Publisher, 2024)
It is widely believed that the confluence of tradition and modernity will propel never-ending evolution of the visual arts. As a testament to this dynamic convergence, the UNIMAS’ Exhibition of Creativity, Innovation, and Technology in the Arts (eCITRA) presents its latest theme of Crossing Frontiers: Bold, Brave, and Beyond. This art exhibition is envisioned as a narrative that delves into the centre of conversation where visual arts and contemporary conditions are fused together to act as a platform for artists in academia to showcase their masterpiece.